Early Retirement: The Impact of Changes in the Benefit Level - Jan H.M. Nelissen (Tinbergen Institute, 2002)
In the Netherlands a transition takes place fromearly retirement schemes, which are characterizedby high implicit tax rates to schemes that have ahigher degree of actuarial fairness. in this paperwe look at the impact of this change at the laborparticipation rates of 55 to 65 years old persons.The analysis has been applied on repeated choiceson the basis of stated preferences. We estimate amixed (or random parameters) logit model. The mostimportant finding is the independent role that isplayed by the number of years for which has builtup pension claims. Its impact does not only run viathe discounted value of future pension streams. Theresults indicate that the change in the earlyretirement schemes will considerably increaselabor participation. A participation rate of 50%for the age group under consideration is within reach.
Keywords: J26; 330; preretirement; labour participation; mixed logit; stated preferences; Flexible Altersgrenze; Erwerbstätigkeit; Niederlande; Logit-Modell